2018
DOI: 10.14202/vetworld.2018.177-180
|View full text |Cite
|
Sign up to set email alerts
|

The effect of moderate exercise on the elevation of Bax/Bcl-2 ratio in oral squamous epithelial cells induced by benzopyrene

Abstract: Aim:The aim of this study was to analyze the effect of moderate exercise on the elevation of Bax/Bcl-2 ratio.Materials and Methods:Eighteen Mus musculus strain Swiss Webster (Balb/c) were divided into three groups (n=6). K1 and K2 had contact with water 3 times/week for 12 weeks, while the members of the K3 group swam 3 times/week for 12 weeks while carrying load weighed 3% of their body weight. After 5 weeks, they were induced with 0.04 ml oleum olivarum (K1), 0.08 mg benzopyrene/0.04 ml oleum olivarum (K2, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In theory, Bcl‐2 prevents apoptosis, while Bax plays a role in promoting apoptosis . In addition, the ratio of Bax/Bcl‐2 is believed to be a reliable indicator of apoptosis . Interestingly, a previous study showed that the knockdown of NLRP3 protects cells from apoptosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, Bcl‐2 prevents apoptosis, while Bax plays a role in promoting apoptosis . In addition, the ratio of Bax/Bcl‐2 is believed to be a reliable indicator of apoptosis . Interestingly, a previous study showed that the knockdown of NLRP3 protects cells from apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…37 In addition, the ratio of Bax/Bcl-2 is believed to be a reliable indicator of apoptosis. 38 Interestingly, a previous study showed that the knockdown of NLRP3 protects cells from apoptosis. 10 This finding suggests that Rg1 can inhibit LPS-induced apoptosis via the TLR4/NF-κB/NLRP3 axis.…”
mentioning
confidence: 99%
“…In Mus musculus test subjects, moderate-intensity exercise (swimming) significantly increased the ratio of Bax/Bcl-2 (n = 6, p = 0.00) and caspase-3 expression (n = 18, p = 0.00) in oral squamous epithelial cells that had been injected with benzopyrene, a carcinogenic substance commonly found in cigarettes. 43,44 The Bax/Bcl-2 ratio, as well as caspase-3, are components in cells that, when their expression increases, receive a signal to perform apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…B[α]P-contaminated foods include vegetables (13 ng/kg), cereals (262 ng/kg), smoked fish (800-13900 ng/kg), and dairy products (11-78 ng/kg) ( 4 ). After entering into the host’s body, B[α]P would bind to the aryl-hydrocarbon receptor and be activated by cytochrome P-4501A1 (CYP1A1) to produce immense size DNA adducts and ROS ( 2 , 5 ), which would inactivate tumor suppressor genes or activate oncogenes, resulting in DNA damage, mutation, and cancer ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%